1997
DOI: 10.1046/j.1365-2273.1997.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of tympanometry in the diagnosis of middle ear effusion

Abstract: Over a 12-month period 501 children (age range 11 months to 15 years) underwent surgery for a possible middle ear effusion. All had tympanometry performed within 2 h of surgery. The results of tympanometry were correlated with the surgical findings in 955 ears. A type-B tympanogram has a high sensitivity (0.91) in predicting middle ear effusion with good specificity (0.79). A type-A tympanogram has a very high specificity (0.99) in predicting a dry middle ear but low sensitivity (0.34). Both the positive (0.91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
3
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 0 publications
5
33
3
13
Order By: Relevance
“…Therefore, DT can also be taken as a measure of a problematic surgery because DT is more common when the child is not assessed on the day of surgery. It has also been proposed that the rate of DT should be zero if the time delay is zero, and thus, the patients should be re-examined with a microscope or tympanometry within 2 h of the operation [2,11]. However, in this study where the time delay from the preoperative exam and surgery was zero due to topical anesthesia, the rate of DT was very low compared to previous studies, but it was still not negligible.…”
Section: Discussioncontrasting
confidence: 53%
“…Therefore, DT can also be taken as a measure of a problematic surgery because DT is more common when the child is not assessed on the day of surgery. It has also been proposed that the rate of DT should be zero if the time delay is zero, and thus, the patients should be re-examined with a microscope or tympanometry within 2 h of the operation [2,11]. However, in this study where the time delay from the preoperative exam and surgery was zero due to topical anesthesia, the rate of DT was very low compared to previous studies, but it was still not negligible.…”
Section: Discussioncontrasting
confidence: 53%
“…Watters et al found that a type B tympanogram had a sensitivity of 91% and specificity of 79% in predicting middle ear effusion in children age 11 months to 15 years [12]. A type C tympanogram is difficult to interpret because most physicians do not suspect effusion unless the peak is rounded and more negative than À150 to À200 mm H 2 O [13].…”
Section: Discussionmentioning
confidence: 98%
“…When a non-suppurative effusion is present, it varies quantitatively and qualitatively. Smallvolume, clinically unapparent effusions may be found at tympanocentesis [Paradise et al, 1976;Orchik et al, 1978;Fiellau-Nikolajsen, 1983;Karma et al, 1989;Toner and Mains, 1990;Babonis et al, 1991;Finitzo et al, 1992;Ovesen et al, 1993;Sassen et al, 1994;van Balen and de Melker, 1994;Watters et al, 1997]. In OME, effusions may be serous or mucoid [Carrie et al, 1992]; the former are mucin poor and associated with less inflammation in terms of immunoglobulin and cytokine levels [Chung et al, 2002;Yabe et al, 2008] and leucocyte infiltration [Tanaka et al, 1986;Yoon et al, 1990] (and are more often of shorter duration [Yoon et al, 1990], unilateral, and in an older age group [Giebink et al, 1982a, b]).…”
Section: Pathological Analysesmentioning
confidence: 99%